ANALISIS KEPUTUSAN PEMBELIAN ATAS KUALITAS PRODUK, HARGA, DAN LOKASI PADA TOKO MEBEL KUSUMA ANTIQ SERENAN - Fani Rianda Adianto; Eny Kustiyah; Ratna Damayanti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
This study aims to determine the effect of furniture purchases partially and simultaneously at Kusuma Antiq Serenan. The research used is quantitative research. The population in this study are all consumers who have purchased furniture at the Kusuma Antiq Serenan Furniture Store with a population of 85 people, so this study is a population study. F test results show that product quality, price and location simultaneously have a positive and significant effect on furniture purchase decisions at Kusuma Antiq Serenan Furniture Store. While the results of the t test showed that the quality of the product partially had a positive and significant effect on purchasing decisions, the price had a positive and significant influence on furniture purchasing decisions at the Kusuma Antiq Serenan Furniture Store and location also had a positive and significant influence on furniture purchase decisions at the Furniture Shop Kusuma Antiq Serenan.